2020
DOI: 10.1038/s41598-019-57397-5
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Off-label Use of Olodaterol and Indacaterol in Denmark, France, and the Netherlands: A Drug Utilization Study

Abstract: To characterize the use of olodaterol and indacaterol in clinical practice and to quantify the off-label use in asthma. Drug utilization study of new users of olodaterol or indacaterol between 2014 and 2017 in the PHARMO Database Network in the Netherlands, the Danish population registers, and the IMS Real-World Evidence Longitudinal Patient Database panels in France. On-label use was defined as use among adults with a recorded diagnosis of COPD. Off-label use was defined as use among adults with a recorded di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…For the discontinuation of aRMMs, the sources of evidence were a non-clinical study (25%) and an observational study (25%). The observational study was a multi-database drug-utilisation study for indacaterol maleate, which was authorised only for use in chronic obstructive pulmonary disease, and had aRMMs to reduce the risks associated with off-label use in asthma; the authors concluded that there was little to no off-label use of indacaterol in the EU [ 10 ]. The data sources could not be identified in two products (50%).…”
Section: Resultsmentioning
confidence: 99%
“…For the discontinuation of aRMMs, the sources of evidence were a non-clinical study (25%) and an observational study (25%). The observational study was a multi-database drug-utilisation study for indacaterol maleate, which was authorised only for use in chronic obstructive pulmonary disease, and had aRMMs to reduce the risks associated with off-label use in asthma; the authors concluded that there was little to no off-label use of indacaterol in the EU [ 10 ]. The data sources could not be identified in two products (50%).…”
Section: Resultsmentioning
confidence: 99%